The Influence of Tunnels on the Surface Structure (University of Thi-Qar Journal for Engineering Sciences, 2023)
The influence of a tunnel must be considered while developing nearby structures in order to prevent the likelihood of tunnel damage. Such an evaluation necessitates a thorough understanding of the soil-structure interaction of buried and surface structures. The focus of this work is study of effect pre-existing of tunnel on shallow foundations. Based on the following criteria: 1. The impact of tunnel depth 2: The influence of foundation sizes on soil carrying capacity, where a practical investigation was undertaken to demonstrate the effect of each of the components described above. The tunnel was made of aluminum. It was placed within sandy soil. The results shows that the tunnel's depth has an impact it is apparent that the lower the depth, the greater the soil carrying capacity, Where three depths were employed, which are 15 , 30, 45 cm measured from the bottom of the used foundations, respectively. The ultimate bearing capacity of the soil increases as the size of the foundation increase.